2014
DOI: 10.1039/c4ra07136k
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of Co3O4porous nanosheets/reduced graphene oxide composites and their excellent supercapacitor performance

Abstract: Porous Co3O4 nanosheets/RGO composite with excellent capacitive performance was prepared through a facile two-step strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 70 publications
4
35
0
Order By: Relevance
“…It was also found that the binding energies of Mn 2p from CoB@MnO2 shifted positively compared to those from the bulk MnOx [39][40][41] . This is due to the fact that when MnOx is highly dispersed on the support, a strong electrostatic field is produced, leading to the positive shift of the Mn 2p binding energy peak 42,43 34,44,45 . In the case of CoB@MnO2, two features were observed.…”
Section: Resultsmentioning
confidence: 99%
“…It was also found that the binding energies of Mn 2p from CoB@MnO2 shifted positively compared to those from the bulk MnOx [39][40][41] . This is due to the fact that when MnOx is highly dispersed on the support, a strong electrostatic field is produced, leading to the positive shift of the Mn 2p binding energy peak 42,43 34,44,45 . In the case of CoB@MnO2, two features were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon‐based materials including carbon particles, carbon nanotubes, carbon nanofibers, graphite, and graphene have been used as electrodes for EDLCs owing to their exceptional properties, such as high surface area, porous structure, chemical inertness, and good electrical conductivity that promote a nanoscopic charge separation at the electrode/electrolyte interface . In addition to carbon, both conducting polymers and transition metal oxides such as manganese oxides (MnO, Mn 2 O 3 , Mn 3 O 4 , MnO 2 ), RuO 2 , Fe 3 O 4 , SnO 2 , NiO, Fe 2 O 3 , TiO 2 , MoO 2 , MoO 3 , CuO, Co 3 O 4 , NiCo 2 O 4 , ZnO, Bi 2 O 3, Nb 2 O 5 , etc., have been used as electrode materials in pseudocapacitors due to their electrochemically active nature and the ability to carry out the Faradaic redox reaction . The electron transfer between the electrodes and the electrolytes comes from the reversible electrochemical doping–redoping with conductive polymers and fast Faradaic redox reactions in transition metal oxides, respectively.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…For as-prepared Co 3 O 4 specimen, four characteristic peaks were observed at 190, 488, 585 and 682 cm À1 , which correspond to the F 1 2g , E g , F 2 2g and A 1g Raman-active modes of the Co 3 O 4 cubic phase, respectively. 25 For the asprepared rGO and RCo5 composite, two broad peaks corresponding to the D band at 1352 cm À1 and G band at 1597 cm À1 were observed, respectively, which showed the existence of rGO. 26 Besides, the peaks of Co 3 O 4 were also observed.…”
Section: Morphology and Structurementioning
confidence: 96%